Theoretical presumptions of the creative industries innovation productivity performance - Krisiukėnienė, Deimantė; Pilinkienė, Vaida (Creativity Studies, 2023)
The development of the concept of creative industries is related to the contribution of culture and creativity to the economy. Creative industries are often associated with innovation.Scientific literature reveals that creative business is more innovative compared to other sectors of the economy. Some authors also note that when assessing the level of innovation, the companies that are closely related to creative industries tend to have higher innovation rates. The concept of creativity is closely related to the major purpose of innovation, i.e. problem solving, while synergy between creativity and economy formulates creative industries theory. Based on the literature, problem solution requires creativity, and some solutions can inspire the emergence of innovation. The major purpose of this article is to provide the theoretical presumptions of the creative industries innovation productivity performance. Applying the method of comparative literature analysis, this article presents a conceptual model that allows to evaluate and compare countries economies in terms of the productivity in the creative industries innovation performance.